Assessment of the presence of hypnocysts of Pyrodinium bahamense Plate var compressum Bohm (1931) in Cancabato Bay, Leyte, Philippines - Acompañado, Alma Suralta; Escalonia Lyn Rudilla; Fumar, Florabel Mendoza; Honor, Marelie Cruzada; Quial, Lorna Abrantes
The presence of hypnocysts of Pyrodinium bahamense var. compressum in Cancabato Bay, Leyte, Philippines was determined from sediments collected during the months of November 1998, January 1999 and February 1999. The highest number of hypnocysts was observed in November, and most of them were concentrated in the inner part of the bay. Except for the sediment load, no significant correlation was found between the number of hypnocyts and ecological parameters measured.